Selective conversion of acetone to mesitylene over tantalum phosphate catalysts. Issue 17 (7th February 2022) - Wu, Zhiyi; Zhang, Jian; Su, Zerui; Lu, Shiyao; Huang, Jianbin; Liang, Yehao; Tan, Tianwei; Xiao, Feng-Shou
Abstract : A tantalum phosphate (TaPO-1) catalyst with abundant strong acid sites is very active for the catalytic conversion of acetone into mesitylene. Abstract : We report the synthesis of a tantalum phosphate catalyst with abundant strong acid sites, which is very active for the catalytic conversion of acetone into mesitylene. Characterizations, kinetic studies, and theoretical results show a relationship between the acidic sites and catalytic performance in this reaction.